The Influence of School Operational Management and Principal's Transformational Leadership on PCK (Pedagogical Content Knowledge) of Elementary School Teachers in Sail District - Indrawati, Sri; Erlisnawati, Erlisnawati; Suanto, Elfis (CV. Tripe Konsultan, 2024)
This study aimed to analyze the influence of school operational management and transformational leadership of the principal on the Pedagogical Content Knowledge (PCK) of elementary school teachers in Sail District. PCK is a key element in teacher professionalism that reflects the ability to integrate pedagogical knowledge with open materials to create effective learning experiences. School operational management plays a role in creating a conducive environment for the development of teacher professionalism, while the transformational leadership of the principal provides inspiration, motivation, and support for improving teacher competence. This study uses a quantitative approach with multiple linear regression analysis methods. The results showed that school operational management had a significant effect on teacher PCK with a regression coefficient value of β = 0.412, p <0.05. The transformational leadership of the principal also had a significant effect on teacher PCK with a value of β = 0.378, p <0.05. Simultaneously, both variables contribute to teacher PCK with a determination coefficient value of R² = 0.621, indicating that 62.1% of teacher PCK variability can be explained by school operational management and principal transformational leadership. The implication of this study is the importance of strengthening the operational management system and principal transformational leadership in improving the quality of learning in elementary schools. Therefore, schools need to implement effective managerial strategies and visionary leadership to optimize teacher competence in teaching.